2008
DOI: 10.1590/s0100-06832008000300021
|View full text |Cite
|
Sign up to set email alerts
|

Impactos da aplicação de biossólidos na microbiota de solos tropicais

Abstract: Termos para indexação: biossólidos, biomassa microbiana, metal pesado, atividade microbiana, carbono orgânico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
9
0
7
Order By: Relevance
“…These pulses appear to be related to the presence of anaerobic microorganisms supplied with the highest SS rate; despite much lower than in the evaluation 9 DAA, the value was significantly higher than in the other treatments (Figure 2). This agrees with results reported by Fernandes et al (2005) and Lambais & Carmo (2008), who also verified increases in CO 2 emission with SS application. Nevertheless, divergences in this type of study are expected for different experimental conditions, that is, the quality and rate of material applied as well as climatic conditions in the experimental area are certainly decisive for the gas emissions analyzed (Chiaradia, 2005).…”
Section: Ch 4 Co 2 and N 2 O Fluxessupporting
confidence: 93%
“…These pulses appear to be related to the presence of anaerobic microorganisms supplied with the highest SS rate; despite much lower than in the evaluation 9 DAA, the value was significantly higher than in the other treatments (Figure 2). This agrees with results reported by Fernandes et al (2005) and Lambais & Carmo (2008), who also verified increases in CO 2 emission with SS application. Nevertheless, divergences in this type of study are expected for different experimental conditions, that is, the quality and rate of material applied as well as climatic conditions in the experimental area are certainly decisive for the gas emissions analyzed (Chiaradia, 2005).…”
Section: Ch 4 Co 2 and N 2 O Fluxessupporting
confidence: 93%
“…Similarly, treatment with sewage sludge exhibited significant emissions (p<0.005), with a maximum value of 6.35±1.17 C m -2 day -1 at the beginning of the experiment. The results showed that the application of sewage sludge and sludge compost increased CO 2 emissions from soil (Chiaradia et al, 2009;Fernandes et al, 2005;Lambais and Carmo, 2008), this process may be associated with increased amount of C available that increases the microbial activity and thus stimulate respiration of autotrophic and heterotrophic microorganisms in the soil (Ball and Smith, 1991). Thus, the application of residues in soil, possibly increased the organic matter content of the soil (Chiaradia et al, 2009;Carmo et al, 2013), which can be determined by the composition of the study materials (De Urzedo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The treatments with sewage sludge and sludge compost received a supplement of KCl, since the potassium content in these residues is low; doses were calculated according to the levels recommended by Raij B. van et al (1996). The calculations to reach the doses were similar to those performed by Lambais and Carmo (2008), considering 30% as the mineralization rate of nitrogen in the sewage sludge and 10% in the compost.…”
Section: Methodsmentioning
confidence: 99%
“…0,113 0,227 Lambais & Carmo (2008), avaliando a aplicação de doses de dois biossólidos em solos de textura distinta (arenosa e argilosa), verificaram que a aplicação do biossólido da ETE-Barueri proporcionou maiores concentrações de C-CBM no solo arenoso quando comparado ao argiloso, exceto após quatro semanas de incubação, enquanto a utilização do biossólido da ETE-Franca resultou em maiores concentrações de C-CBM no solo argiloso do que no arenoso. Comparando esses resultados com o deste trabalho, pode-se afirmar que o C-CBM tende a ser maior em solos de textura argilosa, pois esses autores observaram, após quatro semanas de incubação, maiores concentrações de C-CBM no solo argiloso, quando foram comparados os dois biossólidos, o que também foi observado neste estudo, exceto nas maiores doses.…”
Section: Methodsunclassified